Journey through Islamic art - Robert ,Na'íma bint; Mayo , Diana (London : Mantra Lingua, 2019)
Follow the silken thread of a young girl's imagination through the art of the Islamic world. From great mosques and ancient cities, to magnificent palaces and ornamental gardens
This book is TalkingPEN enabled"--Inside front cover Translation of: Journey through Islamic art
Keywords: English and urdu - text